Necrologio de un extirpador de idolatrías: Pablo Joseph de Arriaga. Documento original del Archivo Romano de la Compañía de Jesús - Chávez, Fabiola (Pontificia Universidad Católica del Perú. Fondo Editorial, 2007)
This paper presents a paleographic transcription of two original documents of the Archivum Romanum Societat Jesu (ARSI) in Rome, referred to the death of Jesuit Priest Pablo Joseph de Arriaga in a province of Peru. The first document has been extracted from the section called Fondo Gesuita: Elogia Defunctorum (1621-1622, 1623). Busta 115, III, 3. The second document is part of the Peru section, volume Peru 21: Vida de los difuntos desta Prov. a del Peru (Life of the Dead in this Province of Peru). 2. a. Via Citanse en carta n. 22, written in Italian of the XVII century.

El artículo presenta una transcripción paleográfica de dos documentos originales del Archivum Romanum Societat Jesu (ARSI), en Roma, referentes a la defunción del Padre Jesuita Pablo Joseph de Arriaga de la provincia del Perú. El primer documento ha sido extraído de la sección denominada Fondo Gesuita: Elogia Defunctorum (1621-1622, 1623). Busta 115, III, 3. El segundo pertenece a la sección Perú, el tomo Perú 21: Vida de los difuntos desta Prov.a del Peru. 2.a. Via Citanse en carta n. 22, escrito en italiano del siglo XVII.
Necrology of an extirpator of idolatries: Pablo Joseph de Arriaga. Original document from the Roman Archive of the Society of Jesus
Keywords: Transcripción; Jesuitas; Perú siglo VII; José Arriaga; https://purl.org/pe-repo/ocde/ford#5.04.03